Implementasi Pendidikan Kepramukaan Sebagai Ekstrakurikuler Wajib Berdasarkan Kurikulum 2013 - Khosyati, Hersy; Supriatna, Irfan (JURIDIKDAS, 2024)
This study describes the implementation of scouting education as a mandatory extracurricular activity based on the 2013 curriculum at State Elementary School 08 Bengkulu. This qualitative study uses a descriptive method. The subjects of the study were the principal, teachers, scout leaders, and students. The instruments used were observation guidelines, interviews, questionnaires, and documentation. Data analysis used the stages of data collection, data presentation, data reduction, and drawing conclusions/verification. The results of the study indicate that the implementation of scouting education at SDN 08 Bengkulu City was carried out with two models, namely the actualization model and the regular model. While scouting education was implemented with a block model in the form of MPLS (Student Orientation Period). The implementation of scouting education with the actualization model and the regular model implemented at State Elementary School 08 Bengkulu has been in accordance with the guidelines set by the Regulation of the Minister of Education and Culture Number 63 of 2014 starting from the planning, process, and assessment stages. Meanwhile, the implementation of scouting education with the block model has been carried out in accordance with the regulations of the Minister of Education and Culture number 63 of 2014. It can be concluded that the implementation of scouting education carried out at State Elementary School 08 Bengkulu is not in accordance with the 2013 curriculum, because in its implementation only the actualization model and the regular model are applied.